Increased Tumor Intrinsic Growth Potential and Decreased Immune Function Orchestrate the Progression of Lung Adenocarcinoma - Zhao, Yue; Shang, Jun; Gao, Jian; Han, Han; Gao, Zhendong; Yan, Yueren; Zheng, Qiang; Ye, Ting; Fu, Fangqiu; Deng, Chaoqiang; Ma, Zelin; Zhang, Yang; et al. (Frontiers in Immunology, 2022)
Background The overall 5-year survival of Lung Cancer was reported to be only ~15%, with lung adenocarcinoma (LUAD) the main pathological subtype. Before developing into invasive stages, LUAD undergoes preinvasive stages of adenocarcinoma in situ (AIS), and minimally invasive adenocarcinoma (MIA), where surgical resection gives a superb 5-year survival rate. Given the dramatic decline of prognosis from pre-invasive to invasive stages, A deeper understanding of key molecular changes driving the progression of lung adenocarcinoma is highly needed. Methods In this study, we performed whole-exome sequencing and RNA-sequencing on surgically resected 24 AIS, 74 MIA, 99 LUAD specimens and their adjacent paired normal tissues. Survival data was obtained by follow-up after surgery. Key molecular events were found by comparing the gene expression profiles of tumors with different stages. Finally, to measure the level of imbalance between tumor intrinsic growth potential and immune microenvironment, a tumor progressive (TP) index was developed to predict tumor progression and patients’ survival outcome, and validated by external datasets. Results As tumors progressed to more invasive stages, they acquired higher growth potential, mutational frequency of tumor suppressor genes, somatic copy number alterations and tumor mutation burden, along with suppressed immune function. To better predict tumor progression and patients' outcome, TP index were built to measure the imbalance between tumor intrinsic growth potential and immune microenvironment. Patients with a higher TP index had significantly worse recurrence-free survival (HR, 10.47; 95% CI, 3.21 – 34.14; p < 0.0001) and overall survival (HR, 4.83e8; 95% CI, 0 – Inf; p = 0.0013). We used TCGA-LUAD dataset for validation and found that patients with a higher TP index had significantly worse overall survival (HR, 1.10; 95% CI, 0.83 – 1.45; p = 0.048), demonstrating the prognostic value of the TP index for lung adenocarcinoma patients. Conclusions The imbalance of tumor intrinsic growth potential and immune function orchestrate the progression of lung adenocarcinoma, which can be measured by TP index. Our study provided new insights into predicting lung adenocarcinoma patients’ survival and new target discovery for lung adenocarcinoma through assessing the imbalance between tumor intrinsic growth potential and immune function.